Inovasi Pembelajaran Fiqih melalui Kinesthetic Games dan Small Group Discussion di Madrasah Diniyah - Ahmad Rosikhul Fahmi; Karina Isnaini; Hilda Najmatul Laili; Syahda Nabila; Sheila Nafilah Sa'adah; Ananda Rona Rahman; Ahmad Nur Roziq Alfian Barik; Ni'matul Mahbubah; Muhammad Aly Multazam; Faridatun Nikmah (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2026)
Islamic religious education at the Madrasah Diniyah level often relies on passive, one-directional teaching methods that reduce madrasah student engagement and long-term retention. This community service study aimed to improve the quality of Fiqh instruction at Madrasah Diniyah Al-Ishlah Kalirejo, Pasuruan, by implementing kinesthetic games, Small Group Discussion (SGD), and visual teaching aids within the framework of Kitab Mabadi’ Fiqhiyyah. A qualitative descriptive approach was employed through four participatory observation sessions, with visual documentation serving as primary data. The program was implemented in four thematic meetings covering funeral prayer procedures, tayammum, hajj simulation (tawaf), and najis classification. Findings indicate that kinesthetic games effectively reduced affective barriers and increased student focus, while the SGD model with a 1:8 mentor-to-student ratio enabled precise procedural correction for motor-based worship practices. The use of concrete teaching aids successfully transformed abstract Fiqh concepts into tangible, memorable knowledge. This study concludes that the integration of active learning methods, small-group mentoring, and visual media within traditional Islamic education settings can significantly enhance student engagement and comprehension. These findings offer a replicable pedagogical model for Madrasah Diniyah educators seeking to modernize instruction while preserving classical curriculum integrity.